2017
DOI: 10.5812/jpr.10133
|View full text |Cite
|
Sign up to set email alerts
|

Methadone Poisoning in Children: A Systematic Review and Meta-Analysis in Iran

Abstract: Context: Symptoms of methadone poisoning, as one of the most dangerous types of poisoning, are very serious in children. Objectives: The aim of this study was to describe causes and clinical symptoms of methadone poisoning in children admitted to hospitals in Iran. Data Sources: Relevant studies published in national and international journals before January 29, 2016 were identified by studying the available databases, including PubMed, Web of Sciences, Google Scholar, Scopus, SID, Iranmedex, MagIran, and Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
(9 reference statements)
2
9
0
Order By: Relevance
“…The most life-threatening toxicity following methadone poisoning is respiratory depression [15]. Central nervous system depression (i.e., drowsiness, reduced consciousness) and miosis were the two most commonly reported clinical signs and symptoms in children with methadone poisoning [7,8,[14][15][16]. The toxicity presentations in the child followed the similar pattern as other reported cases although the child did not develop severe respiratory depression or apnea episodes.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The most life-threatening toxicity following methadone poisoning is respiratory depression [15]. Central nervous system depression (i.e., drowsiness, reduced consciousness) and miosis were the two most commonly reported clinical signs and symptoms in children with methadone poisoning [7,8,[14][15][16]. The toxicity presentations in the child followed the similar pattern as other reported cases although the child did not develop severe respiratory depression or apnea episodes.…”
Section: Discussionmentioning
confidence: 73%
“…Common causes of methadone poisoning in children reported worldwide was due to negligence in safe storage, mistaken as other medicines and intentional use to pacify child by parents [6,7]. There were also foul play cases reported where children were intentionally poisoned by parents who are drug addicts [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rate in our study was 1.01 %, with the mean age of 45.59 ± 24.20 years and majority of these patients were male. A systematic review and meta-analysis conducted on studies from Iran concerning methadone poising in children reported that loss of consciousness, meiotic pupil and drowsiness were the most common presentation [12]. A study conducted in West Virginia on methadone overdose reported that it was more common in men and patients from rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines, methadone, tramadol, morphine and codeine are among the chemical drugs used extensively for treatment of withdrawal symptoms, anxiety, insomnia, epilepsy and muscular spasm [17][18][19]. Use of these drugs without prescription can lead to adverse effects and hospitalisation and also increasing the health costs in the community [17].…”
Section: ■ Discussionmentioning
confidence: 99%